A Multiparametric Assessment of Human Islets Predicts Transplant Outcomes in Diabetic Mice. (7th October 2021) - Komatsu, Hirotake; Qi, Meirigeng; Gonzalez, Nelson; Salgado, Mayra; Medrano, Leonard; Rawson, Jeffrey; Orr, Chris; Omori, Keiko; Isenberg, Jeffrey S.; Kandeel, Fouad; Mullen, Yoko; Al-Abdullah, Ismail H.
Prior to transplantation into individuals with type 1 diabetes, in vitro assays are used to evaluate the quality, function and survival of isolated human islets. In addition to the assessments of these parameters in islet, they can be evaluated by multiparametric morphological scoring (0–10 points) and grading (A, B, C, D, and F) based on islet characteristics (shape, border, integrity, single cells, and diameter). However, correlation between the multiparametric assessment and transplantation outcome has not been fully elucidated. In this study, 55 human islet isolations were scored using this multiparametric assessment. The results were correlated with outcomes after transplantation into immunodeficient diabetic mice. In addition, the multiparametric assessment was compared with oxygen consumption rate of isolated islets as a potential prediction factor for successful transplantations. All islet batches were assessed and found to score: 9 points ( n = 18, Grade A), 8 points ( n = 19, Grade B), and 7 points ( n = 18, Grade B). Islets that scored 9 (Grade A), scored 8 (Grade B) and scored 7 (Grade B) were transplanted into NOD/SCID mice and reversed diabetes in 81.2%, 59.4%, and 33.3% of animals, respectively ( P < 0.0001). Islet scoring and grading correlated well with glycemic control post-transplantation ( P < 0.0001) and reversal rate of diabetes ( P < 0.05). Notably, islet scoring and grading showed stronger correlation with transplantation outcome compared to oxygen consumption rate. Taken together, a multiparametric assessment of isolated human islets was highly predictive of transplantation outcome in diabetic mice.